Supporting autonomy in young people with gender dysphoria: psychotherapy is not conversion therapy - D'Angelo, Roberto (Journal of medical ethics, 2025)
Opinion is divided about the certainty of the evidence base for gender-affirming medical interventions in youth. Proponents claim that these treatments are well supported, while critics claim the poor-quality evidence base warrants extreme caution. Psychotherapy is one of the only available alternatives to the gender-affirming approach. Discussion of the treatment of gender dysphoria in young people is generally framed in terms of two binary approaches: affirmation or conversion. Psychotherapy/exploratory therapy offers a treatment option that lies outside this binary, although it is mistakenly conflated with conversion therapies. Psychotherapy does not impose restrictive gender stereotypes, as is sometimes claimed, but critically examines them. It empowers young people to develop creative solutions to their difficulties and promotes agency and autonomy. Importantly, an exploratory psychotherapeutic process can help to clarify whether gender dysphoria is a carrier for other psychological or social problems that may not be immediately apparent. Psychotherapy can therefore make a significant contribution to the optimal, ethical care of gender-dysphoric young people by ensuring that patients make appropriate, informed decisions about medical interventions which carry risks of harm and have a contested evidence base.